The global diversity of taro: ethnobotany and conservation - Ramanatha, R.V.; Matthews, P.J.; Eyzaguirre, Pablo B.; Hunter, D.; Bioversity International (2010)
Taro is a staple crop for several hundred million small farmers and planters throughout the tropical world. Often associated with Asia and Pacific, it is also important in the Americas and Africa. This book explores the diversity of taros and their uses as well as the status of taro genetic resources in all the major geographic regions where it is grown. While new market opportunities and taro's versatility are responsible for its growing popularity in markets, diseases and climate change also pose ever greater threats to its production and distribution. The current outbreak and spread of the devastating taro leaf blight in West Africa clearly highlights this vulnerability. By taking a global approach to the crop, the authors highlight ways to address new outbreaks of pathogens such as taro leaf blight. Diversity in cultivars is also important in coping and adapting to climate change especially when genetic diversity science and farmer knowledge can be brought together.